ANALYSIS OF HUMAN RESOURCES THAT INFLUENCE CONTRACTOR PERFORMANCE IN BUILDING CONSTRUCTION PROJECT IMPLEMENTATION - Novriadi, Yoppi; Wardi, Wardi; Mizwar, Zuherna (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2024)
This research is to identify and determine human resource factors that influence contractor performance in building construction projects and provide solutions to improve the performance of contractor human resources in Payakumbuh City. This research method uses a quantitative approach. The results of data analysis obtained Determination coefficient value (R-Square) of 0.515 or 51.5%, this shows that all variables competency, motivation, loyalty, compensation, discipline and work environment simultaneously influence the contractor's performance variables, while the remaining 48.5%. Influenced by other variables not tested in the research. From the calculated F value, it is 17,873, while the resulting significant value is 0,000 0,05, it is concluded that all variables competency, motivation, loyalty, compensation, discipline and work environment simultaneously influence the contractor's performance variables. From the results of the t test calculations, it is concluded that competence, motivation and discipline have a partial influence on contractor performance. Based on the largest t value, the most dominant human resource factor is Motivation (X2) because it is found that t count t table (5.415 1.980), and the significance value is 0.000 0.05. Keywords: Human Resources, Performance, Contractors, Projects, Construction